Pregunta
upstudy study bank question image url

Ticutormetians Writing a ruld to deacribe a retalion Triangle RST is rotated \( 90^{\circ} \) counterclockwise about the origin. The result is \( \Delta R^{\prime} S^{\prime} T^{\prime} \), as shown below. (a) The arrows below show that the coordinates on the left are mapped to the coordinates on the right. Fill in the blanks to give the coordinates after the rctation. original coordinates - final coordinates \[ \begin{aligned} R(-8,-2) & \rightarrow R^{\prime}(\square) \\ S(1,-4) & \rightarrow S^{\prime}(\square) \\ T(-2,-6) & \rightarrow r^{\prime}(\square) \end{aligned} \] (b) Choose the general rule below tha: describes the rotation mapping \( \triangle R S T \) to \( \triangle R^{\prime} S^{\prime} T^{\prime} \). \( (x, y) \rightarrow(-y, x) \) \( (x, y) \rightarrow(-x,-y) \) \( (x, y) \rightarrow(y,-x) \) \( (x, y) \rightarrow(x,-y) \) \( (x, y) \rightarrow(-y,-x) \) \( (x, y) \rightarrow(-x, y) \) \( (x, y) \rightarrow\{y, x) \)

Ask by Graham Guerrero. in the United States
Feb 26,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

(a) After rotating 90° counterclockwise: - R(–8, –2) → R'(2, –8) - S(1, –4) → S'(4, 1) - T(–2, –6) → T'(6, –2) (b) The rotation rule is: (x, y) → (–y, x)

Solución

We are given that triangle RST is rotated 90° counterclockwise about the origin. For a rotation of 90° counterclockwise, the general rule is that each point (x, y) is mapped to (–y, x). Step (a): Apply the rule to each vertex. 1. For R(–8, –2):   New coordinates R' = (–(–2), –8) = (2, –8) 2. For S(1, –4):   New coordinates S' = (–(–4), 1) = (4, 1) 3. For T(–2, –6):   New coordinates T' = (–(–6), –2) = (6, –2) Step (b): The correct mapping rule is:   (x, y) → (–y, x)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

To find the coordinates after the \( 90^{\circ} \) counterclockwise rotation, you can use the rule \( (x, y) \rightarrow (-y, x) \). Applying this to the given points: - For \( R(-8, -2) \), we calculate \( R^{\prime} = (-(-2), -8) = (2, -8) \). - For \( S(1, -4) \), we have \( S^{\prime} = (-(-4), 1) = (4, 1) \). - For \( T(-2, -6) \), we find \( T^{\prime} = (-(-6), -2) = (6, -2) \). Now, filling in the blanks, you get: \[ \begin{aligned} R(-8,-2) & \rightarrow R^{\prime}(2, -8) \\ S(1,-4) & \rightarrow S^{\prime}(4, 1) \\ T(-2,-6) & \rightarrow T^{\prime}(6, -2) \end{aligned} \] For part (b), the correct mapping rule that describes the rotation of \( \triangle RST \) to \( \triangle R^{\prime}S^{\prime}T^{\prime} \) is \( (x, y) \rightarrow (-y, x) \). This is the magic behind your shapes spinning around the origin!

preguntas relacionadas

Latest Geometry Questions

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad